Exploring Social Inequality in Argentina: Challenges, Disparities, and Pathways to Equity - Giraudo Vacarezza; Martinez Cruz (Global Writing Academica Researching and Publishing, 2023)
Social inequality in Argentina presents multifaceted challenges that affect various dimensions of society, including income distribution, education, healthcare, employment, and poverty. This comprehensive study delves into the complex landscape of social inequality, employing both quantitative analysis and qualitative insights to uncover its determinants, consequences, and potential pathways to greater equity. The research reveals persistent income disparities, regional inequalities in education and healthcare access, and the impact of historical legacies on contemporary disparities. Economic fluctuations and policy challenges exacerbate social inequality, while social cohesion emerges as a resilience factor. The study's findings contribute to a nuanced understanding of social inequality in Argentina and inform discussions on policies and initiatives aimed at promoting greater equity and well-being.